TEACHING FACTORY DI SMK MUHAMMADIYAH 2 BOROBUDUR MAGELANG - Yoga Guntur Sampurno Ibnu Siswanto (Auto Tech: Jurnal Pendidikan Teknik Otomotif Universitas Muhammadiyah Purworejo, 2015)
The aims of the study are to identify and describe a factual, accurate and systematic about 1)Implementation of teaching factory, and 2) The inhibiting and facilitating factors of itsimplementation at SMK Muhammadiyah 2 Borobudur Magelang.The study used a descriptive approach. The object of study were the Principal andTeachers/Employees at SMK Muhammadiyah 2 Borobudur Magelang. The data were collectedthrough interviews and observations. The data were analyzed using descriptive analysis method.The results showed that 1) The teaching factory at SMK Muhammadiyah 2 Borobudur Magelangalready works quite well because it has the organizational structure, human resources, financialmanagement, equipments, learning, and good cooperation networks, as well as product qualityand acceptable society, 2) Implementation of teaching factory at SMK Muhammadiyah 2Borobudur Magelang not optimal in terms of the involvement of educators in teaching factoryworkshop and suitability of existing skills programs in schools with activities undertaken in theteaching factory program. 3) Factors facilitating the implementation of the teaching factory atSMK Muhammadiyah 2 Borobudur Magelang are: Principal who are experienced and have apassion to develop a teaching factory, teaching factory manager who has a lot of experience forserving in the Department of Industry and Trade of the City of Magelang, the commitment ofemployees, facilities and equipment adequate, and the availability of human resources who havethe competence network in accordance with the work being done. 4) While the inhibiting factorsare: teaching factory building ever collapsed because of Merapi disaster and lack of support fromthe government or bureaucracy.Keywords: Teaching Factory, SMK Muhammadiyah 2 Borobudur MagelangPENDAHULUANSeperti